2007
DOI: 10.1152/ajpgi.00386.2006
|View full text |Cite
|
Sign up to set email alerts
|

Defective hepatocyte aquaporin-8 expression and reduced canalicular membrane water permeability in estrogen-induced cholestasis

Abstract: Carreras FI, Lehmann GL, Ferri D, Tioni MF, Calamita G, Marinelli RA. Defective hepatocyte aquaporin-8 expression and reduced canalicular membrane water permeability in estrogeninduced cholestasis. Am J Physiol Gastrointest Liver Physiol 292: G905-G912, 2007. First published November 16, 2006; doi:10.1152/ajpgi.00386.2006.-Our previous work supports a role for aquaporin-8 (AQP8) water channels in rat hepatocyte bile formation mainly by facilitating the osmotically driven canalicular secretion of water. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 43 publications
8
57
0
Order By: Relevance
“…Experimental cholestasis induced by 17α-ethinylestradiol (EE) has been widely used to investigate in vivo alterations in the expression of hepatocyte membrane transporters in this pathological condition. In a recent work, we found that the protein expression of hepatocyte AQP8 is downregulated in estrogen-induced cholestasis possibly by posttranscriptional mechanisms, without significant changes in the sinusoidal AQP9 [59] . In fact, complementary studies in primary cultured rat hepatocytes with protease inhibitors indicated that estrogen-induced AQP8 downregulation was mediated by increased lysosomal degradation.…”
Section: Pathophysiological Significance Of Hepatocyte Aqps: Cholestasismentioning
confidence: 78%
“…Experimental cholestasis induced by 17α-ethinylestradiol (EE) has been widely used to investigate in vivo alterations in the expression of hepatocyte membrane transporters in this pathological condition. In a recent work, we found that the protein expression of hepatocyte AQP8 is downregulated in estrogen-induced cholestasis possibly by posttranscriptional mechanisms, without significant changes in the sinusoidal AQP9 [59] . In fact, complementary studies in primary cultured rat hepatocytes with protease inhibitors indicated that estrogen-induced AQP8 downregulation was mediated by increased lysosomal degradation.…”
Section: Pathophysiological Significance Of Hepatocyte Aqps: Cholestasismentioning
confidence: 78%
“…In a recent study by Carreras et al (2007), adult male Wistar rats were administered 5 mg ethinylestradiol/kg BW/day for 5 days to induce intrahepatic cholestasis. Treated animals had decreased BW and increased liver weight indicating a general toxic response, whereas ethinylestradiol-induced cholestasis did not seem to change the protein level or localization of AQP9.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the total level of AQP9 expression in the liver is higher in male than in female rats, also having a more localized periacinous expression (Nicchia et al 2001). Nevertheless, in adult male rats, ethinyl estradiol at a dose sufficiently high to cause cholestasis had no effect on AQP9 expression (Carreras et al 2007). …”
mentioning
confidence: 98%
“…In line with this is the fact that different animal models of cholestasis show defective canalicular AQP protein expression. (9)(10)(11)(12) In this context, it is conceivable that AQP gene transfer may help to improve certain cholestatic disorders.…”
Section: To the Editormentioning
confidence: 99%
“…In line with this is the fact that different animal models of cholestasis show defective canalicular AQP protein expression. (9)(10)(11)(12) In this context, it is conceivable that AQP gene transfer may help to improve certain cholestatic disorders.According to the editorial, studies in AQP8 knockout mice provide evidence against a role of canalicular AQP8 in bile secretion. (8) In that study, bile was not collected, and the conclusion was based on the fact that AQP8 knockout mice show only mild dietary fat misprocessing.…”
mentioning
confidence: 99%